Bendamustine and rituximab in combination with lenalidomide in patients with chronic lymphocytic leukemia. (9th February 2016) - Maurer, Christian; Pflug, Natali; Bahlo, Jasmin; Kluth, Sandra; Rhein, Christina; Cramer, Paula; Gross‐Ophoff, Carolin; Langerbeins, Petra; Fink, Anna‐Maria; Eichhorst, Barbara; Kreuzer, Karl‐Anton; Fischer, Norbert; et al.
Abstract: Purpose: A phase I/II trial to assess safety and efficacy of the combination bendamustine, rituximab, and lenalidomide (BRL) in patients with chronic lymphocytic leukemia (CLL). Patients and Methods: Seventeen relapsed or refractory (R/R) and five previously untreated (FL) CLL patients were enrolled in the trial. In the R/R cohort, four different dose levels of lenalidomide (maximum 15 mg/d) were used. In the FL cohort, lenalidomide was dose escalated from 5 mg/d to 15 mg/d. Bendamustine was used at doses of 50 or 90 mg/m 2 for R/R or FL treatment, respectively. 375 mg/m 2 Rituximab were used for the first and 500 mg/m 2 for subsequent treatment courses. Treatment consisted of up to six courses of 28 d. Results: The maximal tolerable dose of lenalidomide was 5 mg/d. The response rate was 47.1% in R/R and 60% in FL patients. Median progression‐free survival was 8.0 months. Median overall survival was 22.9 and 12.3 months, respectively, in R/R and FL patients. Grade 3/4 hematological toxicity was observed in 71.4%, and severe infections in 47.6% of patients. Due to high toxicity and low response rate of BRL, the trial was closed prematurely. Conclusion: BRL was associated with a high toxicity rate, a high number of treatment interruptions, and a low remission rate. Therefore, BRL cannot be considered an appropriate treatment option for patients with CLL.